‘We are all in the same boat’: How societal discontent affects intention to help during the COVID-19 pandemic - Resta, Elena; Mula, Silvana; Baldner, Conrad; Di Santo, Daniela; Maximilian, Agostini; Belanger, Jocelyn J; Gutzkow, Ben; Kreienkamp, Jannis; Abakoumkin, Georgios; Abdul Khaiyom, Jamilah Hanum; PsyCorona, Collaboration; Leander, N Pontus (John Wiley and Sons Ltd, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has cau-sed a global health crisis. Consequently, many countries have adopted restrictive measures that caused a substantial change in society. Within this framework, it is reasonable to suppose that a sentiment of societal discontent, defined as generalized concern about the precarious state of society, has arisen. Literature shows that collectively experienced sit-uations can motivate people to help each other. Since societal discontent is conceptualized as a collective phenomenon, we argue that it could influence intention to help others, particu-larly those who suffer from coronavirus. Thus, in the present study, we aimed (a) to explore the relationship between soci-etal discontent and intention to help at the individual level and (b) to investigate a possible moderating effect of societal discontent at the country level on this relationship. To fulfil our purposes, we used data collected in 42 countries (N = 61,734) from the PsyCorona Survey, a cross-national longitudinal study. Results of multilevel analysis showed that, when societal discontent is experienced by the entire com-munity, individuals dissatisfied with society are more prone to help others. Testing the model with longitudinal data (N = 3,817) confirmed our results. Implications for those find-ings are discussed in relation to crisis management. Please refer to the Supplementary Material section to find this arti-cle's Community and Social Impact Statement.